LASER APPLICATIONS IN HEALTH: PHYSICAL BASES AND THERAPEUTIC APPLICATIONS - Ferreira, Ana Caroline da Silva; Farias, Thayssa Gomes; da Silva, Marcelle Abreu; de Paoli, Flávia; da Fonseca, Adenilson de Souza (Seven Editora, 2026)
The characteristics of laser radiation—monochromaticity, coherence, and collimation—allow for therapeutic applications in different areas of health. For this purpose, physical parameters such as wavelength, which determines affinity with chromophores (water, melanin, hemoglobin, for example), beam power, irradiance, and fluence are critical for reproducibility and therapeutic efficacy. Laser-tissue interactions are classified into photochemical, photothermal, and photomechanical processes. Photobiomodulation stands out, as it is based on photochemical processes and promotes beneficial cellular effects without inducing thermal damage. In contrast, high-power lasers are explored for their ability to promote coagulation and ablation of biological tissues. This chapter discusses the applications of lasers in the health field, grounding their effectiveness in understanding the physical basis and mechanisms of interaction with the biological environment. Applications in Dentistry (cavity healing and preparation), Medicine (epilation, resurfacing, panretinal photocoagulation, and kidney stone fragmentation), and Physiotherapy (pain reduction and musculoskeletal tissue repair) are presented. Safety is emphasized as a fundamental requirement in clinical protocols, and dosimetry and continuous technical training of professionals are essential to ensure the effectiveness of laser-based therapies.